TRAINING AND ASSISTANCE IN THE USE OF INSTAGRAM LIVE IN IMPROVING THE EXISTENCE OF MSMEs - Alamanda, Amelia Rizky; Nadyalita, Sherina (LPPM Univ. Ibn Khaldun Bogor, 2022)
The presence of technology and the internet makes it easier for people to go shopping, especially online rather than shopping conventionally. MSME actors also feel the same way, namely the convenience of the internet or social media in carrying out business activities such as advertising, sales promotion, direct marketing, and personal selling to develop their businesses. However, it turns out that there are still many MSMEs that are constrained to digitally transform through social media, one of which is Instagram. Based on data reported by Suara.com, the number of Instagram users in Indonesia in 2022 has reached 99.15 million people. So in this case, students through community service programs can play a role in being directly involved in providing socialization and educating MSMEs with door-to-door methods and online meetings regarding the Instagram social media platform, especially the use of the Instagram Live feature to increase the existence of MSMEs and help expand the reach of their business target market.